The American Heritage picture dictionary (Boston Houghton Mifflin, 2007)
A dictionary for preschool and early elementary grades, with each word defined by a sentence using the word to describe the object or activity portrayed in the accompanying illustration
Linguistic notions
1
Keywords: English language -- Dictionaries, Juvenile; Picture dictionaries, English -- Juvenile literature; Picture dictionaries